Polycyclic Aromatic Hydrocarbon-DNA Adducts in Gulf of Mexico Sperm Whale Skin Biopsies Collected in 2012. (10th February 2021) - Poirier, Miriam C; Marsili, Letizia; Fossi, Maria Cristina; Godard-Codding, Céline A. J; Hernandez-Ramon, Elena E; Si, Nancy; Divi, Kathyayini V; Divi, Rao L; Kerr, Iain; Wise, John Pierce; Wise, Catherine F; Wise, Sandra S; et al.
Abstract: The northern Gulf of Mexico has a long history of polycyclic aromatic hydrocarbon (PAH) contamination from anthropogenic activities, natural oil seepages, and the 2010 Deepwater Horizon explosion and oil spill. The continental shelf of the same area is a known breeding ground for sperm whales ( Physeter macrocephalus ). To evaluate PAH-DNA damage, a biomarker for potential cancer risk, we compared skin biopsies collected from Gulf of Mexico sperm whales in 2012 with skin biopsies collected from sperm whales in areas of the Pacific Ocean in 1999–2001. All samples were obtained by crossbow and comprised both epidermis and subcutaneous blubber. To evaluate exposure, 7 carcinogenic PAHs were analyzed in lipids extracted from Pacific Ocean sperm whale blubber, pooled by sex, and location. To evaluate PAH-DNA damage, portions of all tissue samples were formalin-fixed, paraffin-embedded, sectioned, and examined for PAH-DNA adducts by immunohistochemistry (IHC) using an antiserum elicited against benzo[ a ]pyrene-modified DNA, which crossreacts with several high molecular weight carcinogenic PAHs bound to DNA. The IHC showed widespread epidermal nuclear localization of PAH-DNA adducts in the Gulf of Mexico whales ( n = 15) but not in the Pacific Ocean whales ( n = 4). A standard semiquantitative scoring system revealed significantly higher PAH-DNA adducts in the Gulf of Mexico whales compared to the whales from the Pacific Ocean study ( p = .0002).